Spectrum of Dermatological Manifestations among Travelers Presenting at aTravel Medicine Center in Western Nepal - Sandeep Gupta; Saroj Pokhrel; Saraswoti Neupane; Prativa Pandey (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Skin disorders are among the most common reasons for travelers to seek medical care during and after travel. There is limited data on the spectrum of dermatoses reported among travelers during travel especially in South Asian continent.